THE JOURNEY AND PERFORMANCE OF E-TAX INVOICING IN INDONESIA: A SYSTEMATIC LITERATUR REVIEW - Latifa, Fatania; Ritchi, Hamzah; Tanzil, Nanny Dewi (Jurnal Riset Akuntansi Dan Bisnis Airlangga, 2023)
This study aims to analyze the development of research results in relation to the implementation, issues, and problems of performance of e-tax invoicing in Indonesia; to determine benefits of e-tax invoicing implementation for improving compliance; how do users perceive the implementation e-tax invoicing; and what is the impact of the performance of e-tax invoicing in increasing state revenue. This study uses a Systematic Literature Review method that systematically identify and review journal articles to answer the research questions. The PRISMA protocol was established by selecting articles obtained from the Google Scholar database, identifying them based on the year of the article from 2014 to 2022, screening by applying quality assessment and criteria of limitations, and reviewing the eligibility of articles resulting in the remaining 28 articles from accredited journal. The results indicate that: (i) on the subject research of the development of e-tax invoicing in Indonesia discussed the implementation of e-tax invoicing, and analyzed the issues and problems arising from changes in e-tax invoicing from one period to another; (ii) e-tax invoicing plays a role in increasing taxpayer compliance in administration of Value Added Tax reporting; (iii) the perceptions of e-tax invoice users about the usability and convenience of e-tax invoicing, have affected the use of etax invoicing, and the quality of the system affects user satisfaction; (iv) e-tax invoicing ultimately lead to an increase in state revenue. This study is expected to enrich the literature related to e-tax invoicing in Indonesia so that other researchers can develop another topic on e-tax invoicing. Practically, this study also can be used by the government to develop policies and revise regulations related to tax collection, especially Value Added Tax. It can also provide consideration to tax payer in deciding to use e-tax invoicing from Directorate General of Taxation or host-to-host etax invoicing.